2013
DOI: 10.1371/journal.pntd.0002010
|View full text |Cite
|
Sign up to set email alerts
|

Towards Rational Use of Antibiotics for Suspected Secondary Infections in Buruli Ulcer Patients

Abstract: BackgroundThe emerging disease Buruli ulcer is treated with streptomycin and rifampicin and surgery if necessary. Frequently other antibiotics are used during treatment.Methods/Principal FindingsInformation on prescribing behavior of antibiotics for suspected secondary infections and for prophylactic use was collected retrospectively. Of 185 patients that started treatment for Buruli ulcer in different centers in Ghana and Bénin 51 were admitted. Forty of these 51 admitted patients (78%) received at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
(26 reference statements)
0
31
0
1
Order By: Relevance
“…described an association between paradoxical reactions, trunk localization, large lesions, and genetic factors. They showed that individuals carrying homozygous ins/ins genotype of 3′UTR TGTG 285 polymorphism in the SLC11A1 gene have increased risk of paradoxical reactions . In BU, paradoxical reactions may result from reversal of the mycolactone toxin induced immune‐inhibitory state via the antibiotic‐mediated killing of MU allowing intense immunological reaction to develop against the persisting mycobacterial agents .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…described an association between paradoxical reactions, trunk localization, large lesions, and genetic factors. They showed that individuals carrying homozygous ins/ins genotype of 3′UTR TGTG 285 polymorphism in the SLC11A1 gene have increased risk of paradoxical reactions . In BU, paradoxical reactions may result from reversal of the mycolactone toxin induced immune‐inhibitory state via the antibiotic‐mediated killing of MU allowing intense immunological reaction to develop against the persisting mycobacterial agents .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…). Studies documenting the occurrence of secondary infection with the isolation of infecting pathogens and the growth of microbial pathogens in the presence of mycolactone have given evidence to support the occurrence of secondary infection in BU and proven that mycolactone does not prevent its occurrence. Secondary infection in BU should be suspected when a wound becomes painful or develops cellulitis .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…This practice undeniably extends the consultation period, which has the consequences listed above. This phytotherapy, often used under dubious conditions, could also be the cause of the superinfections observed [37]. Collaboration with traditional healers could be considered in addition to raising public awareness to refer cases early on.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, secondary infections of BU lesions were shown to be with organisms such as Staphylococcus aureus and Pseudomonas aeruginosa before treatment, P. aeruginosa during treatment, and P. aeruginosa or Proteus miriabilis after treatment. 93 Notably, 78% of the patients with BU on admission in Ghana and Benin used other antibiotics apart from the standard combination of streptomycin and rifampicin, 94 and S. aureus in BU lesions showed a high frequency of resistance to the first-line drugs used in Ghana as well as the presence of methicillin-resistant S. aureus. Whole genome sequencing of S. aureus isolates from patients with BU and the subsequent analysis of sequencing data using the SeqSphere scheme reveal likely patient-to-patient transmission events in a health care setting in Ghana indicating a need for the implementation of improved hygiene protocols in health care settings, where patients with BU receive wound care.…”
Section: Secondary Infectionmentioning
confidence: 99%
“…If there are signs of secondary bacterial infection, a swab should be taken for culture, but this cannot always guide individual care. 94 Dressings like those that release bactericidal nitric oxide 84,85 or that retain M. ulcerans and other wound pathogens such as Dialkyl carbamoyl chloride-coated dressings 97 may improve healing by reducing the bacterial load in BUs, but these have yet to be tested.…”
Section: Secondary Infectionmentioning
confidence: 99%